2016
DOI: 10.1038/ejcn.2016.193
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between lifestyle and MTHFR polymorphisms on homocysteine concentrations in young adults belonging to the 1982 Pelotas Birth Cohort

Abstract: BACKGROUND/OBJECTIVES: Homocysteine (Hcy) is a key intermediate in methionine metabolism. A high plasma concentration of Hcy is an independent risk factor for cardiovascular diseases among other determinants. In this study, we aimed to investigate the interactions between methylenetetrahydrofolate reductase enzyme gene (MTHFR) polymorphisms and lifestyle variables (smoking, alcohol intake and physical activity) on Hcy concentrations in a young Brazilian population. SUBJECTS/METHODS: The study population compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
2
13
1
Order By: Relevance
“…It should be noted that the Hcy level in homozygous mutant of MTHFR 1298CC was signi cantly lower than that in wild type 1298AA (13.74 vs 19.46) (shown in Table 5). Similar to the results of IO Oliveira's study (42) , compared with 1298AA group, the Hcy concentration of MTHFR 1298 CC decreased in male -10% and in female -5% respectively. In addition to us, Bruno Zappacosta's study (43) got the same result that Hcy value was higher in the wild-type (1298 AA), and lower in the homozygote's mutation (1298 CC).…”
Section: Discussionsupporting
confidence: 87%
“…It should be noted that the Hcy level in homozygous mutant of MTHFR 1298CC was signi cantly lower than that in wild type 1298AA (13.74 vs 19.46) (shown in Table 5). Similar to the results of IO Oliveira's study (42) , compared with 1298AA group, the Hcy concentration of MTHFR 1298 CC decreased in male -10% and in female -5% respectively. In addition to us, Bruno Zappacosta's study (43) got the same result that Hcy value was higher in the wild-type (1298 AA), and lower in the homozygote's mutation (1298 CC).…”
Section: Discussionsupporting
confidence: 87%
“…Homocysteine, an intermediate sulfhydryl-containing amino acid, is synthesized by the liver in a reaction involving the removal of the methyl group from methionine 19 , 20 . High level of Hcy is mainly found in patients with a nutritional deficiency of B vitamins as well as being present in genetic diseases where there is an insufficient level of cystathionine beta-synthase enzyme (CβS) or a mutation inn the enzyme 5,10-methylenetetrahydrofolate reductase (MTHFR).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between micronutrients and genetic variants on cardiometabolic traits was examined by five Brazilian studies (81)(82)(83)(84)(85). A cross-sectional study of 335 healthy young adults (81), observed a pronounced increase in systolic blood pressure (SBP) (P interaction = 0.016) among carriers of the "G" allele of Angiotensinogen (AGT) SNP rs699 with a higher plasma magnesium (209.3 mg).…”
Section: Interactions Between Micronutrients and Genetic Variants On ...mentioning
confidence: 99%